THE EFFECT OF FOMO (FEAR OF MISSING OUT) ON PRODUCT OR SERVICE PURCHASE DECISIONS AMONG GENERATION Z: LITERATURE REVIEW - Setiawan, Heru Dwi (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study is a literature review that aims to comprehensively analyze the influence of Fear of Missing Out (FOMO) on the decision to purchase products/services among Generation Z. Method: This study examines various literature that discusses the relationship between FOMO, social media use, exposure to digital marketing strategies, and purchasing decisions. Results: The results of this study are expected to provide insight for marketers, academics, and practitioners in understanding the dynamics of Generation Z consumer behavior in the digital era. Novelty: FOMO, as a psychological phenomenon characterized by anxiety about losing information or trending experiences, is considered to have an important role in shaping the consumption behavior of this generation that is active on social media.